Analisis Penerapan Sistem Dan Prosedur Akuntansi Pengelolaan Dana Desa (Studi Kasus di Desa Wairkoja Kecamatan Kewapante Kabupaten Sikka) - Claurensia Isabella Moning; Henrikus Herdi; Emilianus Eo Kutu Goo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
This research aims to analyze the implementation of accounting systems and procedures for managing village funds in Wairkoja Village, Kewapante District, Sikka Regency. This research is descriptive research using a qualitative approach. The data sources used are primary data and secondary data. Data collection techniques include interviews and documentation. The results of this research show that the accounting system and procedures for managing village funds in Wairkoja Village, Kewapante District, Sikkame Regency include planning, implementation, management, reporting and accountability. The Wairkoja Village Government has followed the Minister of Home Affairs Regulation Number 113 of 2014, by always holding deliberations involving the Wairkoja Village community in planning village funds to realize village development programs and community empowerment by building infrastructure such as village offices, making rebate roads, providing housing assistance. habitable and building community toilets/KM, as well as increasing village community empowerment, such as training and assistance for ikat weaving groups, and assistance with livestock and fertilizer for the community.